The Utilization of Eco-Enzyme as An Alternative to Emphasize the Household Wastes - Cut Juliana; Diza Hamzah (Universitas Serambi Mekkah, 2024)
The enhancement of human activity has significantly influenced the increase in waste production. The Ministry of Environment and Forestry 2022 reports that Indonesia produced 68.7 tons of waste per year, and the largest waste contribution came from household activities. Garbage is an agent of disease transmission, so it must be managed well. Make an eco-enzyme to discard household waste materials, especially kitchen waste. Therefore, eco-enzymes can be used as an alternative to reduce household waste production. This study is a quasi-experiment research with a one-group pre and post-test design. This research aims to explore the community knowledge before and after being given education about eco-enzymes. The population in this study was all mothers who had toddlers in Lam Teungoh village, Peukan Bada District Aceh Besar Regency. Some mothers with toddlers were used as research samples of 55 people using purposive sampling techniques—data was collected using a questionnaire that the researcher had designed. The data analysis used a paired T-test with a confidence interval of 95%. The result showed that there was an increase in the average knowledge score of mothers of toddlers before (57,09) and after being given eco-enzyme counseling (79,3182), with a significant value (p-value) of 0.000. This shows that eco-enzyme promotion can increase the knowledge of mothers of toddlers significantly at the 95% confidence interval (p<0.05).